Lossen Rearrangement of p-Toluenesulfonates of N-Oxyimides in Basic Condition, Theoretical Study, and Molecular Docking - Kijewska, Monika; Sharfalddin, Abeer A.; Jaremko, Łukasz; Cal, Marta; Setner, Bartosz; Siczek, Miłosz; Stefanowicz, Piotr; Hussien, Mostafa A.; Emwas, Abdul-Hamid; Jaremko, Mariusz (Frontiers in Chemistry, 2021)
The sulfonic esters of N-oxyimides are a group of compounds with a wide range of biological activities, as well as a unique reactivity towards amines. They undergo this reaction with primary amines and other nucleophilic reagents according to a Lossen-like rearrangement. The reaction is initiated by nucleophilic attack on a carbonyl group in the succinimide ring followed by isocyanate formation, which next interacts with another nucleophile molecule forming an addition product (e.g., ureido or urethane derivative). However, the secondary amines are also susceptible to other reactions leading to products containing the maleimide ring formed by sulphonic acid elimination. In the case of tertiary amines, this reaction is predominant. In order to explain the phenomenon of the reactivity of the N- oxyimides towards different types of amines, we employed various spectroscopic and X-ray approaches as well as DFT calculation. Results suggest that the basicity of the amine used for the reaction plays a crucial role in the reaction mechanism that eventually dominates the entire chemical process. Moreover, we applied molecular docking to investigate the ability of the products to act as serine protease inhibitors using human leukocyte elastase (HLE).